Developing Islamic English instructional materials based on school-based curriculum - Zaitun Qamariah (Journal on English as a Foreign Language, 2015)
This study was a research and development (R&D) which is basically aimed at developing English instructional materials based on School-based Curriculum for the first-year students of MAN Model Palangka Raya. This study involved: need analysis, reference study, material development, expert validation, try out (empirical validation), and revision. The data were gathered through observation, questionnaires, interview, and validation technique.  The result of the need analysis shows that the students are in need of English instructional materials relevant to their major content needs and school characteristics. However, the existing English instructional materials used by the teachers and the first-grade students of MAN Model Palangka Raya as a senior high school with Islamic feature still served from available published course books which are too general and still do not reflect the need of the students and particular characteristics of the school. English instructional materials developed in this study is intended to develop English instructional materials which could provide a set of instructional materials to accomodate the Islamic characteristics and the needs of the first-year students of MAN Model Palangka Raya. For the purpose, the materials were adopted and adapted from some Islamic textbooks and Islamic reading websites.